Primary Malignant Lymphomas o.f Stomach.: staging, Diagnosis and Treatment - Perdomo, Roberto; Sica, Miguel A; Pereyra Borrelli, César; de los Santos, Julio (Cirugía del Uruguay, 1980)
Malignant lymphomas can be described as tumors likely to occur in gastric region, in their primary stage, greatly resembling the more frequent carcinoma. It is important that the surgeon should be alert before this possibility when establishing diagnosis, since these tumors have better prognosis.